Risks and Prognoses of Alzheimer's Disease and Vascular Dementia in Patients With Insomnia: A Nationwide Population-Based Study - Baek, Min Seok; Han, Kyungdo; Kwon, Hyuk-Sung; Lee, Yong-ho; Cho, Hanna; Lyoo, Chul Hyoung (Frontiers in Neurology, 2021)
This study aimed to investigate the risk and prognosis of Alzheimer’s disease (AD) and vascular dementia (VD) in patients with insomnia using the National Health Insurance Service database covering the entire population of the Republic of Korea from 2007 to 2014. In total, 2,796,871 patients aged 40 years or older with insomnia were enrolled, and 5,593,742 controls were matched using a Greedy digit match algorithm. Mortality and the rate of admission to a long-term care facility were estimated using multivariable Cox analysis. Of all patients with insomnia, 138,270 (4.94%) and 26,706 (0.96%) were newly diagnosed with AD and VD, respectively. The incidence rate ratios for AD and VD were 1.73 and 2.10, respectively, in patients with insomnia compared with those without. Higher mortality rates and long-term care facility admission rates were also observed in patients with dementia in the insomnia group. Known cardiovascular risk factors showed interactions with the effects of insomnia on the risk of AD and VD. However, the effects of insomnia on the incidence of AD and VD were consistent between the groups with and without cardiovascular risk factors. Insomnia is a medically modifiable and policy-accessible risk factor and prognostic marker of AD and VD.